2019
DOI: 10.1158/1055-9965.epi-18-0584
|View full text |Cite
|
Sign up to set email alerts
|

A Pragmatic Testing-Eligibility Framework for Population Mutation Screening: The Example of BRCA1/2

Abstract: Background: Eligibility guidelines for genetic testing may be revisited, given technological advances, plummeting costs, and proposals for population mutation screening. A key property of eligibility criteria is the tradeoff between the number of mutation carriers identified versus population members tested. We assess the fractions of mutation carriers identified, versus women undergoing mutation testing, for BRCA1/2 founder mutation screening in U.S. Ashkenazi-Jewish women.Methods: BRCA1/2 carrier probabiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Whether the high prevalence of clinically important germline mutations in OC patients justifies population-wide screening is a vivid matter of debate [44][45][46][47][48]. We emphasize that we found BRCA1/2 mutations in 14.5% of OC patients with no family cancer history who would currently not be revealed presymptomatically without population screening.…”
Section: Discussionmentioning
confidence: 68%
“…Whether the high prevalence of clinically important germline mutations in OC patients justifies population-wide screening is a vivid matter of debate [44][45][46][47][48]. We emphasize that we found BRCA1/2 mutations in 14.5% of OC patients with no family cancer history who would currently not be revealed presymptomatically without population screening.…”
Section: Discussionmentioning
confidence: 68%
“…First, Ashkenazi Jewish ancestry without a personal cancer history is now included as a scenario for which genetic testing may be considered. The rate of the 3 founder pathogenic variants in this population is 2.2% to 2.5%, [1][2][3] which is equivalent to a level of risk for some other testing criteria, such as breast cancer diagnosed at age #45 years. In addition, studies have shown that genetic testing based on clinical guidelines emphasizing a family history of breast, ovarian, prostate, or other cancers missed approximately 38% to 56% of mutation carriers with Ashkenazi Jewish ancestry, 1,2,4,5 providing some evidence to support population-based genetic testing among the Ashkenazi Jewish population.…”
Section: Testing Criteria For High-penetrance Breast And/or Ovarian Cmentioning
confidence: 95%
“…Instead, a lower risk threshold, below 10%, might identify most all mutation-carriers, yet avoid unnecessary testing for most women. We recently showed that a low 0.78% risk-threshold would identify 80% of Ashkenazi-Jewish mutation-carriers yet test only 44% of Ashkenazi-Jewish women(24). We use AUC, MRS, NBI, and Net Benefit to throw light on properties of BRCAPRO to select women for BRCA1/2 testing at risk thresholds between 0%−10%.…”
Section: Informativeness Of Risk Models To Select People For Brca1/2 mentioning
confidence: 99%
“…We calculated each volunteer’s risk of carrying a mutation, based on their self-reported family-history of breast/ovarian cancers, using BRCAPRO. Here M is the BRCAPRO risk score, and because BRCAPRO is a well-calibrated risk model(24), m 0 = R , i.e. the cutpoint m 0 equals the risk threshold R .…”
Section: Informativeness Of Risk Models To Select People For Brca1/2 mentioning
confidence: 99%
See 1 more Smart Citation